Blocking effect on transmission of Ne7+ ions through nanocapillaries. (July 2015) - Herczku, P; Juhász, Z; Kovács, S T S; Rácz, R; Biri, S; Sulik, B
Synopsis: Systematic investigation was carried out on the guided transmission of 22 Ne 7+ ions through nanocapillaries in polycarbonate (PC) foil from 3 to 6-keV kinetic energy range. At 3-keV energy a strong blocking effect was observed contrary to the 6-keV case, where a stable transmission was developed.